PROSES MORFOLOGIS REDUPLIKASI DALAM BUKU GENERASI OPTIMIS KARYA AHMAD RIFA’I RIF’AN - Asngadi Rofiq; Khisbiya Ayatuna Nuzula (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to determine the types of reduplication (rephrase) that are in the motivational book for the Optimist Generation by Rifa'i Rif'an. The types of reduplication that are dominated in the book Generasi Optimis by Rifa'i Rif'an are complete reduplications, compared to other types of repetition, such as partial repetition, repetition combined with affix affixing processes and repetition with phoneme changes. The research method used is descriptive qualitative. The research data is the morphological process of using reduplication in a book entitled Generasi Optimis by Ahmad Rifa'i Rif'an. The data collection techniques used in this study were note taking and reading techniques. The results of research on the morphological process of reduplication in the book Optimist Generation by Ahmad Rifa'i Rif'an are one hundred forty-three with details of all eighty-three repetitions, nineteen partial repetitions, and forty-one repetitions with affixes. While the meaning of reduplication used in this study is the meaning which states the meaning of 'many' which is related to the basic form totaling forty-one, states that the meaning of 'many' is not related to the basic form of three, states the meaning that 'the action is in the basic form. performed repeatedly amounting to four, expressing the meaning of 'the highest level that can be achieved amounts to four.